2022
DOI: 10.1093/eurheartj/ehac298
|View full text |Cite
|
Sign up to set email alerts
|

Implantable defibrillators in primary prevention of genetic arrhythmias. A shocking choice?

Abstract: Many previously unexplained life-threatening ventricular arrhythmias and sudden cardiac deaths (SCDs) in young individuals are now recognized to be genetic in nature and are ascribed to a growing number of distinct inherited arrhythmogenic diseases. These include hypertrophic cardiomyopathy, arrhythmogenic cardiomyopathy, long QT syndrome, Brugada syndrome, catecholaminergic polymorphic ventricular tachycardia (VT), and short QT syndrome. Because of their lower frequency compared to coronary disease, risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 172 publications
(185 reference statements)
0
8
0
Order By: Relevance
“…221,222 Risk assessment models have been proposed for predicting the risk of life-threatening ventricular arrhythmias (including SCD), 223,224 however their practical use requires further validation. 225 Recently, a risk prediction model to estimates the 5-year risk of incident ventricular arrhythmias in ARVC has been developed (ARVCrisk. com) and validated.…”
Section: Arrhythmogenic (Right Ventricular) Cardiomyopathymentioning
confidence: 99%
See 1 more Smart Citation
“…221,222 Risk assessment models have been proposed for predicting the risk of life-threatening ventricular arrhythmias (including SCD), 223,224 however their practical use requires further validation. 225 Recently, a risk prediction model to estimates the 5-year risk of incident ventricular arrhythmias in ARVC has been developed (ARVCrisk. com) and validated.…”
Section: Arrhythmogenic (Right Ventricular) Cardiomyopathymentioning
confidence: 99%
“…RV fractional area change <23%), male sex, T‐wave inversion, QRS dispersion, non‐sustained VT and LV dysfunction have been associated with an increased risk of life‐threatening ventricular arrhythmias and SCD 221,222 . Risk assessment models have been proposed for predicting the risk of life‐threatening ventricular arrhythmias (including SCD), 223,224 however their practical use requires further validation 225 . Recently, a risk prediction model to estimates the 5‐year risk of incident ventricular arrhythmias in ARVC has been developed (http://arvcrisk.com) and validated 224,226 .…”
Section: Arrhythmogenic (Right Ventricular) Cardiomyopathymentioning
confidence: 99%
“…Before these calculators can be recommended for clinical use, rigorous validation studies are needed to assess their superiority in the prediction of SCD (rather than appropriate ICD discharges) in comparison with the traditional ‘single risk factor’ approach. 20 …”
Section: Introductionmentioning
confidence: 99%
“…In these patients, the decision to implant an ICD should be made on individual basis, by assessing the overall clinical profile, the age, the strength of the risk factor(s) identified, the level of SCD risk that is acceptable to the patient, and, most important, the potential high risk of serious complications over time. 20 Implantation of an ICD is not generally indicated in asymptomatic patients with no risk factors and healthy mutation carriers who have a low risk of malignant VAs. The performance of the 2015 TF consensus algorithm to guide ICD implantation in patients with S/ACM was validated by clinical studies which demonstrated that the algorithm accurately differentiated survival from any sustained VT or VF among the different ICD class indications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation